Wardowski's Contraction and Fixed Point Technique for Solving Systems of Functional and Integral Equations. (16th November 2021) - Hammad, Hasanen A.; Bota, Monica-Felicia; Guran, Liliana
Abstract : In this manuscript, some tripled fixed point results are presented in the framework of complete metric spaces. Furthermore, Wardowski's contraction was mainly applied to discuss some theoretical results with and without a directed graph under suitable assertions. Moreover, some consequences and supportive examples are derived to strengthen the main results. In the last part of the paper, the obtained theoretical results are used to find a unique solution to a system of functional and integral equations.